Oxidative Stress and NLRP3-Inflammasome Activity as Significant Drivers of Diabetic Cardiovascular Complications: Therapeutic Implications - Sharma, Arpeeta; Tate, Mitchel; Mathew, Geetha; Vince, James E.; Ritchie, Rebecca H.; de Haan, Judy B. (Frontiers in Physiology, 2018)
It is now increasingly appreciated that inflammation is not limited to the control of pathogens by the host, but rather that sterile inflammation which occurs in the absence of viral or bacterial pathogens, accompanies numerous disease states, none more so than the complications that arise as a result of hyperglycaemia. Individuals with type 1 or type 2 diabetes mellitus (T1D, T2D) are at increased risk of developing cardiac and vascular complications. Glucose and blood pressure lowering therapies have not stopped the advance of these morbidities that often lead to fatal heart attacks and/or stroke. A unifying mechanism of hyperglycemia-induced cellular damage was initially proposed to link elevated blood glucose levels with oxidative stress and the dysregulation of metabolic pathways. Pre-clinical evidence has, in most cases, supported this notion. However, therapeutic strategies to lessen oxidative stress in clinical trials has not proved efficacious, most likely due to indiscriminate targeting by antioxidants such as vitamins. Recent evidence now suggests that oxidative stress is a major driver of inflammation and vice versa, with the latest findings suggesting not only a key role for inflammatory pathways underpinning metabolic and haemodynamic dysfunction in diabetes, but furthermore that these perturbations are driven by activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome. This review will address these latest findings with an aim of highlighting the interconnectivity between oxidative stress, NLRP3 activation and inflammation as it pertains to cardiac and vascular injury sustained by diabetes. Current therapeutic strategies to lessen both oxidative stress and inflammation will be emphasized. This will be placed in the context of improving the burden of these diabetic complications.